Accommodation Strategy of PT Inko Forwarding in Building a Cross-Cultural Virtual Team with Taiwanese Companies - Pradana, Dywa Hanif; Bertha Sri Eko; Rismi Juliadi (LPPM Stikosa - AWS, 2024)
Advancements in communication technology have opened up opportunities for companies to engage in virtual business collaborations. Establishing cross-cultural virtual teams and devising effective strategies for their operation can significantly benefit companies. The research aims to explore the challenges and hurdles faced when working in cross-cultural virtual teams, strategies for forming and managing such teams, as well as communication accommodation strategies within them. Communication Accommodation Theory serves as the theoretical framework, utilizing a descriptive qualitative approach through case study methodology. In-depth interviews were conducted for data collection. Findings reveal the implementation of convergence accommodation strategies by each virtual team studied, particularly exemplified by Inko Forwarding. The company aims to nurture business relationships with agents to achieve specific objectives by establishing networks. To succeed in these endeavors, understanding cultural nuances and employing Communication Accommodation Theory strategies to enhance communication quality within virtual teams are crucial.